Altitude‐related shift of relative abundance from insect to sunbird pollination in Elaeagnus umbellata (Elaeagnaceae). Issue 6 (29th December 2020) - Pi, Hua‐Qiang; Quan, Qiu‐Mei; Wu, Bo; Lv, Xiao‐Wen; Shen, Li‐Min; Huang, Shuang‐Quan
Abstract: The evolution of floral traits has been thought to be influenced by local, effective pollinators. However, little attention has been paid to the possibility that altitudinal variation in floral traits could be mediated by local pollinator functional groups, particularly a shift from bees to birds. Plant size, floral traits, pollinators and their pollination roles were investigated in the spring‐flowering shrub Elaeagnus umbellata (Elaeagnaceae) at three altitudes (1160, 1676, and 2050 m) in Minshan, Sichuan Province, on the northern rim of the Hengduan Mountains, southwest China. Compared to lower altitudes, higher‐altitude plants were smaller but the floral tubes were longer, with a larger volume of nectar of lower sugar concentration but with a greater proportion of sucrose. The visitation frequency of bees decreased with altitude, whereas the sunbirds did the opposite. Birds and bees foraged for nectar but not pollen, and birds deposited more pollen grains per visit relative to bees and least were syrphid flies. Excluding birds decreased seed set at high but not at mid‐ or low altitude. Our study of E. umbellata revealed an association between altitudinal variation in floral traits and a change in the relative abundance of the major pollinators with altitude from majority bees to majority sunbirds. Although abiotic factors also tend to vary with altitude and can affect floral traits, nectar properties of "pro‐bird" pollination were observed at high altitude. Abstract : Although the shift from bee to bird pollination appears repeatedly in multiple plant groups, an altitude‐related shift of pollination systems as well as the floral traits within species is little known. We found higher‐altitude plants were smaller but the floral tubes were longer, with a larger volume of nectar of lower sugar concentration but with a greater proportion of sucrose than lower‐altitude plants in an autumn olive, Elaeagnus umbellata . The altitudinal variation in floral traits associated with a change in the relative abundance of the major pollinators with altitude from bees to sunbirds.